Mastering enterprise JavaBeans 3.0 - Sriganesh, Rima Patel. 4 0 16; Brose, Gerald,;Silverman, Micah; 5 (Indianapolis, IN : Wiley, 2006)
A guide to using Enterprise Java Beans 3.0 that covers implementing beans, basic and advanced concepts of Java Persistence API defined entities, Web services, securing EJB applications, and more.
Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; JavaBeans.;JavaBeans.; Java (Computer program language);Java (Computer program language); 20; 2